The dolines above the collapse chambers of Postojnska jama - Šebela, Stanka (Acta carsologica, 1996)
On the surfaces above the passages of Postojnska Jama there are 22 dolines and two collapse dolines. Slightly less than half the dolines (40,9 %) developed above collapse chambers. These are formed in regionally the most significant tectonically fractured zones and are genetically related to tectonically crushed zones. Collapse chambers represent places of the youngest transformations of cave passages. Vertical percolation in the vandose zone is in these places normally very good, evidenced by chimneys on the ceilings of collapse chambers. The dolines above collapse chambers in Postojnska Jama are found above Rov Brez Imena, Pisani Rov and Koncertna Dvorana
Keywords: karst; kras (geologija); kraške jame; kraški pojavi; List of caves in Slovenia; Postojna Cave; Postojnska jama; vrtače